Role of Ascorbic Acid in Drought Stress Tolerance of Wheat Plant Triticum aestivum L. - AL-Kazzaz , Amel Ghanim Muhmood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Drought is a major abiotic stress, severely affecting the physiological processes and growth of plants. The present investigation aimed to evaluate the impacts of drought stress with three periods for irrigation: every 3 days(control), every 6 days, and every 12 days and foliar spray with different concentrations of ascorbic acid (0, 75, 150, 225) mg.L-1 on the wheat plant. Pots experiment was conducted as a completely randomized design with three replications in the green house, Department of Biology, College of Education for Pure Science (Ibn Al- Haitham), University of Baghdad, during the growing season, 2018 – 2019. The results indicated that drought stress decreased plant growth and hastened the senescence of flag leaves, which is significantly associated with a decrease in the quality and quantity of grain yield. Foliar spray with ascorbic acid enhanced plant drought tolerance in terms of plant height, shoot dry weight, flag leaf traits (flag leaf area, flag leaf chlorophyll and the concentration of macronutrients such as nitrogen, phosphorous, potassium) and some yield components (spike length, grain weight. pot-1 and protein percentage of grains). The results indicated the efficiency of ascorbic acid foliar spray on vegetative growth, flag leaf traits and some yield components of wheat plants affected by drought stress and the superiority to 150 mg.L-1 ascorbic acid in which plants can resist the unfavorable drought stress periods(12 days).